2022
DOI: 10.3390/w14020153
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Design of a Stepped Spillway Aerator

Abstract: Stepped spillways are frequently limited to specific discharges under around 30 m2/s due to concerns about potential cavitation damages. A small air concentration can prevent such damages and the design of bottom aerators is well established for smooth chutes. The purpose of this study is to systematically investigate the performance of a deflector aerator at the beginning of stepped chutes. Six parameters (chute angle, step height, approach flow depth, approach flow Froude number, deflector angle and deflecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In light of the results obtained herein, it is considered advisable not to adopt design unit discharges considerably larger than 15-20 m 2 /s in the steeply sloping stepped spillways of large dams, provided that artificial air entrainment is not introduced in the flow (e.g., by piers or aerators). In [61][62][63][64], for example, it is shown that the use of aerators may enable the considerably increase of the maximum (permissible) unit discharge. In addition, for dam spillways of small to moderate heights, larger unit discharges may also be considered adequate, provided that σ > σ c is assured down the chute on the non-aerated flow region [27,29,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the results obtained herein, it is considered advisable not to adopt design unit discharges considerably larger than 15-20 m 2 /s in the steeply sloping stepped spillways of large dams, provided that artificial air entrainment is not introduced in the flow (e.g., by piers or aerators). In [61][62][63][64], for example, it is shown that the use of aerators may enable the considerably increase of the maximum (permissible) unit discharge. In addition, for dam spillways of small to moderate heights, larger unit discharges may also be considered adequate, provided that σ > σ c is assured down the chute on the non-aerated flow region [27,29,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…This risk can be mitigated by implementing a specially designed aerator in the upstream reach of the stepped chute. Based on systematic laboratory experiments on a large-scale model, Terrier et al [27] present the performance and design of a spillway aerator arranged at the beginning of a stepped chute. They systematically analyzed the lower and upper surfaces of the jet issued by the deflector and could derive empirical equations for the lower and upper effective takeoff angles.…”
Section: Spillway Transport Structuresmentioning
confidence: 99%
“…The authors demonstrate that the air entrainment coefficient of the aerator could be derived from the relative jet length and propose an empirical relationship, thus able to obtain the air entrainment coefficient as a function of the Froude number and the deflector geometry. Finally, Terrier et al [27] give relations for estimating the average and bottom air concentrations at relevant locations along the flow, which provide a sufficient value to counter cavitation damages. The design procedure for a stepped spillway aerator is illustrated with a practical example.…”
Section: Spillway Transport Structuresmentioning
confidence: 99%
“…In this case, we have: (15) where h l is the losses of friction along the length behind the outlet section of the hole; The definition of the losses of friction along the length is made in Table 1.…”
Section: Study Of the Spillway Option No 2 With Pressure Mode Of Skip...mentioning
confidence: 99%
“…The issues of designing spillway structures considered in papers [4][5][6][7][8][9][10][11][12][13][14][15][16] should also help in answering the questions about researching the need to improve the existing system of management and planning of hydropower plants within the framework of interacting power and water management systems, using the criteria of economic, social and ecological efficiency. And as indicated in [17], planning long-term power balances and increasing their feasibility should include forecast scenarios of water inflow into reservoirs for up to 1 year and their monthly adjustment, ensuring the safe operation of hydro-technical structures.…”
mentioning
confidence: 99%